Speed limiter integrated fatigue analyzer (SLIFA): engineering design and concept - Hadi Pranoto; A.M. Leman; Fajar Anggara; Muhammad Kholil (Universitas Ahmad Dahlan, 2019)
Main issue in urban transportation system is traffic accident which caused by several factors where there are two factors that has a significant contribution in accident are overspeed and fatigue. Therefore, main objective of this research is to develop Speed Limiter Integrated Analyzer (SLIFA). This device will be controlling the speed by cutting off the fuel supply to the engine when driver's fatigue or speed are beyond limitation. This research was consists of four steps which are Step 1 is study literature on types of vehicle. Step 2, detail engineering design that is focused in this research. Step 3 is describing the target of SLIFA installation. Step 4 is fabricating and testing of SLIFA on truck and bus in range of July 2017 to January 2018. The result shows the appropriate voltage for speed at 70 km/h is 10.7 volt for limiting the speed. The traffic accident has succesfully decreased up to 47% after SLIFA installed on truck and bus. It can be concluded that the SLIFA application on transportation especially on truck and bus was very recommended to reduce traffic accident and play an appropriate government regulation.